PENGARUH TRADISI MESATUA SEBAGAI METODE PENDEKATAN KELOMPOK TEMAN SEBAYA DALAM UPAYA MERUBAH PERILAKU MENYIKAT GIGI SISWA SDN 5 SAYAN UBUD GIANYAR TAHUN 2016 - I Nyoman Wirata (Poltekkes Kemenkes Denpasar, 2018)
Abstract. Strategic effort to embody the community empowerment in the school is the peer group form so that the choosen students who are trained to be able to play an active role as a clean and healthy driver for delivering subjects and messages in health promotion using mesatua as a dimension in Balinese culture , The aim of this study is to determine the effect of mesatua tradition as a peer group approach in changing the tooth brushing behavior of SD 5 Sayan Ubud students in 2016. This study is the experimental with pretest-posttest without control group design study was conducted at SD 5 Sayan Ubud, Gianyar.Using 79 students as sample. Datas was analyzed by the comparability of the Wilcoxon Match Pairs test and correlation of the Spearman test.Results of Wilcoxon Match Pairs test showed that there were significant differences in knowledge, attitudes and skills of students in toothbrushing (p0.05). Mesatua tradition as the peer group approach method influence on the tooth brushing behavior and oral hygiene status of students. Conclusion of this study is the mesatua tradition as the peer group approach method influence on the tooth brushing behavior of SD 5 Sayan Ubud students in 2016.Keywords: mesatua, toothbrushing behavior, peer group approach